Dietary Mango Ginger May Enhance the Exercise Performance and Reduces Lipid Profile when Combined with Treadmill Running in a Rat Model - Şahin, Kazım; Tuzcu, Mehmet; Orhan, Cemal; Şahin, Nurhan; Akdemir, Fatih; Pala, Ragip; Juturu, Vijaya (Wiley, 2017)
[Abstract Not Available]
Experimental Biology (EB) Annual Meeting -- APR 22-26, 2017 -- Chicago, IL